2009
DOI: 10.1021/tx900158h
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in the Human Metabolism of an Arsenic-Containing Carbohydrate, 2′,3′-Dihydroxypropyl 5-deoxy-5-dimethylarsinoyl-β-d-riboside, a Naturally Occurring Arsenical in Seafood

Abstract: We report studies on the variability in human metabolism of an oxo-arsenosugar involving the ingestion of a chemically synthesized arsenosugar and quantitative determination of the arsenic metabolites in urine and serum by HPLC coupled with arsenic-selective mass spectrometric detection (ICPMS, inductively coupled plasma mass spectrometry). The total, four-day, urinary excretion of arsenic for six volunteers ranged widely from ca. 4-95%. The arsenic metabolites present in the urine also showed great variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 20 publications
(31 reference statements)
4
83
1
Order By: Relevance
“…Thio-arsenicals have been recognized as toxic in studies on human cells [132,133]. Thio-DMA (V), the sulphur analogue of DMA (V) and a mammalian metabolite after arsenosugar consumption [51,[134][135][136], has shown strong cytotoxic effects in cultured human lung and bladder cells [130,137].…”
Section: Mechanisms and Toxicity Of Arsenic Compounds Occurring In Sementioning
confidence: 99%
See 1 more Smart Citation
“…Thio-arsenicals have been recognized as toxic in studies on human cells [132,133]. Thio-DMA (V), the sulphur analogue of DMA (V) and a mammalian metabolite after arsenosugar consumption [51,[134][135][136], has shown strong cytotoxic effects in cultured human lung and bladder cells [130,137].…”
Section: Mechanisms and Toxicity Of Arsenic Compounds Occurring In Sementioning
confidence: 99%
“…An experimental study in human volunteers suggest that both MA and DMA are readily absorbed across the GI-tract with about 75 % excreted in the urine after four days [49]. In another human study, arsenosugars seem to be almost completely absorbed (> 80 %) [50], possibly with considerable inter-individual variation [51]. A metabolic study of arsenolipids in two volunteers showed that arsenolipids were readily absorbed and converted to water-soluble arsenicals; 90 % were excreted in the urine during 66 h [52].…”
mentioning
confidence: 99%
“…found that approximately 80 % of arsenosugar was excreted in urine in one male volunteer four days after ingestion, giving evidence of almost complete absorption in humans. However, more recent data based on urinary excretion suggest considerable individual variability in the absorption of arsenosugars (Raml et al, 2009).…”
Section: Absorptionmentioning
confidence: 99%
“…Arsenosugars and arsenolipids are metabolised by humans to dimethylarsinate (Raml et al, 2009;Schmeisser et al, 2006), but no other information is available regarding their toxicity.…”
Section: Organic Arsenicmentioning
confidence: 99%
“…PCC 7120 are also capable of producing arsenosugars (Miyashita et al, 2012). Recent work suggests that human ingestion of arsenosugars and arsenolipids might be harmful with potential for release of toxic metabolites with arsenolipids posing the potential for toxicity at levels comparable with inorganic arsenite (Harrington et al, 2008;Raml et al, 2009;Newcombe et al, 2010;Feldmann and Krupp, 2011;Leffers et al, 2013a, b;Meyer et al, 2014). Further laboratory work is needed to verify the functionality of arsM and to determine to what extent Prochlorococcus is capable of methylating arsenicals and what organic compounds are synthesized.…”
Section: Discussionmentioning
confidence: 99%